'It's not designed for women at all': exploring service providers' perspectives of working in the Victorian criminal justice system. Issue 2 (3rd April 2021) - Franich, Gabriela; Sandy, Larissa; Stone, Una
ABSTRACT: Gender, crime, incarceration, mental health and trauma have a complex history of interaction. This project aimed to explore service providers' experiences of supporting incarcerated women with a mental illness in Victoria, Australia. Data collection involved in-depth interviews with service providers, and data were analysed using thematic analysis. The results of the analysis revealed that service providers valued holistic and trauma-informed models of practice, which were essential in supporting criminalised women. However, a lack of resources and pervasive misogynistic attitudes in the criminal justice sector hindered service delivery. During interviews, research participants spoke at length about the challenges and constraints they faced working in Victoria's criminal justice system and how this affected their ability to support their clients. It was found that service providers felt that their ability to support criminalised women was impeded by difficulty navigating the service sector and the incompatibility of holistic, gender-responsive models with an androcentric justice system.